Do not perish outdated CDS/ISIS data: ABCD ILS from the same family is there to make it alive. Issue 5 (1st December 2020) - Shoeb, Md. Zahid Hossain; Rahman, Md. Mukhlesur
Abstract : Purpose: This paper aims to outline the migration of outdated computerized documentation system/integrated set for information systems (CDS/ISIS) database in to fully functional Web-based Automatización de Bibliotecas y Centros de Documentación (ABCD) integrated library system (ILS), which is derived from the the United Nations educational, scientific and cultural organization (UNESCO) CDS/ISIS software technology. Design/methodology/approach: The existing integrated set for information systems (ISIS) tags were needed to be remapped as per the tag of MARC-like or structured bibliographic format database by editing integrated set for information systems print formats. Moreover, a sequence of tasks was required to complete the whole process. The major procedures were accomplished as exporting ISIS data into .iso format, creating ABCD database and uploading .iso file into the new database. The next part was configuration and connection with the Web interface after editing PFT. Findings: CDS/ISIS users who have data in the international organization for standardization format on old versions of CDS/ISIS software applications now have the opportunity to migrate their data into the new application. The detailed process had been outlined not an only successful method of migrating outdated valuable records, also creation of ABCD database. Originality/value: This paper may help the users of CDS/ISIS or WinISIS to migrate for ABCD and not to expire or give up their valuable data. This is one of the best ways to migrate ISIS data to ABCD with proven functionality. A specific aim of Automatización de Bibliotecas y Centros de Documentación Integrated Library System is to offer a tool for librarians, rather than information communications technology technicians, which is achieved by taking library and information science principles.